Sound transmission loss of ETICS cladding systems considering the structure-borne transmission via the mechanical fixings: Numerical prediction model and experimental evaluation. (July 2017) - Santoni, Andrea; Bonfiglio, Paolo; Davy, John L.; Fausti, Patrizio; Pompoli, Francesco; Pagnoncelli, Luigi
Abstract: Nowadays it is common to increase the acoustic and thermal performance of building façades using the External Thermal Insulation Composite System ( ETICS ). In this paper a prediction model to evaluate the sound transmission loss provided by such systems, also considering the mechanical bridges that connect the insulating slabs to the basic wall, is presented. The model is developed within the transfer matrix method framework and it is based on a well established decoupled approach. The different formulations presented by several authors to take into account the structure-borne sound transmission through the mechanical connections in multilayer and double-plate elements are not suitable to analyse these kind of building partitions, since they are addressed only to thin plate elements and lightweight porous or fibrous materials. Unfortunately, the different layers that the ETICS consists of need a more sophisticated definition within the transfer matrix method. Therefore, a new model, developed for these specific elements, is proposed. The computation of all the terms and the necessary assumptions are accurately described and their validity is verified with experimental data. Finally, the reliability of the model is investigated by comparing the numerical results with measured transmission loss.